Palinoestratigrafia e interpretação paleoambiental da formação Manacapuru, região de Presidente Figueiredo (AM), Lochkoviano da bacia do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
The Manacapuru Formation, Amazonas Basin, crops out on the banks of the federal highway BR-174 in the region of Presidente Figueiredo, state of Amazonas. A faciological and palynological analysis was carried out in the place with the aiming to contribute to paleoenvironmental understanding in which the unit was deposited, as well its chronostratigraphic position. The faciology analysis took into account parameters such as texture, granulometry and structures and allowed the recognition of 6 predominantly muddy facies interbedded with sandy lenses, they are: Massive Mudstone, Shale, Parallel-laminated Sandstone, Wave-laminated Sandstone, Hummocky cross-laminated Sanstone and Swaley cross-laminated Sandstone. It was possible to observe the presence of macrofossil content associated with some described facies. The processes related to them suggest that the deposition occurred in an offshore region inserted in a shallow marine shelf and constantly influenced by storm. A total of 27 samples were collected for palynological analysis and forwarded for processing according to standard procedure at Marleni Marques Toigo Palynology Laboratory, Federal University of Rio Grande do Sul. The processing took place from acid attacks to the inorganic fraction of the rock. The recovered palynomorphs comprise sporomorph (representatives of fungi and spores), amorphous organic matter, scolecodont, acritarch and chitinozoa, the latter being used as a tool for biostratigraphic purposes. The recovered specimens were duly described and illustrated. The genus Ancyrochitina and Angochitina stand out as the most diverse. It was possible to identify an assemblage of lower Lochkovian, attributed to the Upper Manacapuru Formation and whose characteristic species are Angochitina filosa, Cingulochitina ervensis, Lagenochitina navicula and Pterochitina megavelata. It was also possible to identify an intense reworking in the exposure, evidenced by the presence of paleofaunas ranging from Ludfordian to Pridolian, which may be associated to the constant storm events that reached the shelf.
Keywords: Quitinozoários; Devoniano; Formação Manacapuru; Bacia do Amazonas; CIÊNCIAS EXATAS E DA TERRA: GEOCIÊNCIAS: GEOLOGIA: PALEONTOLOGIA ESTRATIGRÁFICA